POLITICAL EDUCATION CONNECTION WITH STRATEGIC MANAGEMENT - Rochidin Wahab (VISION, 2018)
Political education with strategic management is very close, strategic management without the political will experience lameness and uncontrollable, so politics is also providing guidance on the management strategies in order to implement the function. The need for the development authority is decentralized, because the implications for the freedom to manage the behaviors that gave birth to fair, transparent, more independent and responsible.